FATTY ACID COMPOSITION AND PROSTAGLANDIN CONTENT OF THE RED SEAWEED Gracilaria sp. FROM INDONESIA - Muhammad Ikbal Illijas; Arifuddin Arifuddin; Luqman Saleh; Yutaka Itabashi (Indonesian Aquaculture Journal, 2012)
High content of polyunsaturated fatty acids (PUFAs) such as arachidonic and eicosapentaenoic acids are typical for the red alga. Analysis of fatty acid composition and prostaglandin content was conducted in the red alga Gracilaria sp. from Indonesia. Total lipid of the alga was extracted with CHCl3-MeOH (2:1, v/v). Analysis of the fatty acids composition was performed on gas chromatography (GC) equipped with omega wax column (30 m x 0,32 mm i.d., Supelco, PA, USA) and analysis of prostaglandins were carried out by HPLC on ODS column (Mightysil RP-18 GP, 250 mm x 4.6 mm, 5 μm). The content of fatty acids high for were palmitic acid (50%) and arachidonic acid (26.9%), whereas prostaglandin E2 was identified and found lower concentration (44.2 μg/gram total lipid).